Paired-Associative Stimulation-Induced Long-term Potentiation-Like Motor Cortex Plasticity in Healthy Adolescents - Lee, Jonathan C.; Croarkin, Paul E.; Ameis, Stephanie H.; Sun, Yinming; Blumberger, Daniel M.; Rajji, Tarek K.; Daskalakis, Zafiris J. (Frontiers in Psychiatry, 2017)
Objective: The objective of this study was to evaluate the feasibility of using paired associative stimulation (PAS) to study excitatory and inhibitory plasticity in adolescents while examining variables that may moderate plasticity (such as sex and environment). Methods: We recruited 34 healthy adolescents (aged 13-19, 13 males, 21 females). To evaluate excitatory plasticity, we compared mean motor evoked potentials (MEPs) elicited by single-pulse TMS before and after PAS at 0, 15, and 30 min. To evaluate inhibitory plasticity, we concomitantly evaluated the cortical silent period (CSP) elicited by single-pulse TMS in the contracted hand before and after PAS at 0, 15, and 30 min. Results: All participants completed PAS procedures. No adverse events occurred. PAS was well-tolerated. PAS-induced significant increases in the ratio of post-PAS MEP to pre-PAS MEP amplitudes (p<0.01) at all post-PAS intervals. Neither socioeconomic status, nor sex, was associated with post-PAS MEP changes. PAS-induced significant CSP lengthening in males but not female adolescents. Conclusions: PAS is a feasible, safe, and well-tolerated index of adolescent motor cortical plasticity. Gender may influence PAS-induced changes in cortical inhibition. PAS is safe and well-tolerated by healthy adolescents and may be a novel tool with which to study adolescent neuroplasticity.